Characterization of Hydroxyapatite Nanoparticles from Fish Scale Waste and Its Adsorption of Carotenoids - Kongsri, Supalak; Ladawan Na Ayuttaya, Pattarapond; Yookhum, Sorasart; Techawongstein, Suchila; Chanthai, Saksit (Asian Journal of Chemistry, 2013)
Hydroxyapatite nanoparticles (FHAp) of fish scales were prepared by alkaline heat treatment method. Chemical structure, morphology and thermal property of solid powder obtained were characterized by surface analysis, X-ray diffraction and Fourier transform infrared spectroscopy, scanning electron microscopy and thermal analysis in comparison with those of chitosan. The results showed that the nano-sized particles of hydroxyapatite nanoparticles have high porosity and surface roughness. In application, the potential use of hydroxyapatite nanoparticles as adsorbent for b-carotene/lycopene from tomato extract was investigated under optimized conditions. The adsorption isotherms demonstrated that the adsorption behaviours of the carotenoids on both hydroxyapatite nanoparticles and chitosan substrates were well fitted with both of Langmuir and Freundlich isotherms. However, difference in sensitivity and selectivity of its hydrophobic interactions of the conjugated alkene molecule to the ionic surface of hydroxyapatite nanoparticles was somewhat pronounced comparing with chitosan.